Malang, Image of the City, kota. ANALISIS ELEMEN IMAGE OF THE CITY DI KOTA MALANG - Jalaluddin Mubarok (Universitas Islam Malang, 2023)
Urban development in an area must have progressed with the passage of human civilization, so that in general urban development not only develops in quantity or number of inhabitants, but also in terms of the development of architectural art, other architectural elements. This makes researchers feel important in terms of studying and analyzing urban development, especially in urban development according to Kevin Lynch's theory, the Image of the City. This is seen from its development must have been very different from the theory and application in urban and urban areas of a city in a particular region. This also encourages researchers to map the area of one of the cities in East Java, namely the city of Malang. Because the location is in an area that is experiencing very rapid growth and development, so there needs to be a study and mapping of urban elements in the city of Malang. So that the output that will be taken from this study is a layout of the urban area of Malang city and details the elements of the Image of the City. Keywords: Malang; Image of the City; City.